Justice of administrative responsibility - Chupris, Olga I. (Journal of the Belarusian State University. Law, 2020)
Different approaches to assessing the justice of administrative responsibility are available in science and in practice. Therefore, a complex of aspects in which justice is reflected is considered. Six aspects are analyzed: consolidation of administrative responsibility for specific acts by formulating prohibitions, typifying administrative penalties, as well as determining the types of penalties and their sizes in the sanctions of norms; bringing to administrative responsibility by imposing a fair measure of administrative penalties; Liability, or its implementation, by enduring by a person who violated the established procedure; getting victims satisfaction from the punishment of the offender; reduction of the state of things that took place before the commission of the offense; exemption from administrative responsibility. The proposal on the desirability of direct fixing in the Code of Administrative Offenses of the Republic of Belarus of the purpose of administrative responsibility which is the achievement of justice, is formulated.